Podcast e educação: um estudo de caso - Jesus, Wagner Brito de [UNESP] (2014)
The debate over the usage of digital technology as a supporting tool on the learning process of children and young adults has been growing lately, with the internet's educational use being the main topic in the discussion. Internet has been the converging point for every other media format: newspapers, radio and TV. From that, new media can arise so can news ways of use for the conventional media. Podcast is one of those examples. If we consider the Podcast as a media format with great potential, will it be possible to use this technology as a tool in the current educational system? Our target is to debate the Podcast's classroom potential via case study. We hope that this work's result signals not the correct usage of such media, but guide us true the case study (with the Podcast from Portugal) e the possible applications of this media in the educational effort. Therefore, we shall point out the major educational field yet to be explored in Brazil through the employment of the language and technology of the Podcast